2000
DOI: 10.1007/s11912-000-0114-9
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and the impact of systemic therapy on hormonal status following treatment for breast cancer

Abstract: Issues of long-term toxicity from treatment for breast cancer, including the induction of premature ovarian failure, appear to be of increasing importance for breast cancer survivors. The incidence of treatment-related amenorrhea is related to patient age and to the treatment regimen. Whereas the induction of ovarian failure may be advantageous with respect to breast cancer outcome, it is not clear that there is any advantage to permanent menopause over reversible hormonal manipulations. In addition, menopause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…This novel finding has substantial clinical relevance for pre-menopausal women with cancer requiring cytotoxic chemotherapy. Because CRA can impact prognosis [14], fertility [15], and menopausal symptoms [16], in women with breast cancer, pre-chemotherapy AMH measurement may ultimately have utility in clinical decision-making. Furthermore, identifying a pre-treatment predictor of later ovarian dysfunction could be particularly important for reproductive decision-making, as the commonly recommended fertility preservation techniques for breast cancer patients (e.g., oocyte and embryo cryopreservation) are most effective before gonadotoxic therapies are given.…”
Section: Discussionmentioning
confidence: 99%
“…This novel finding has substantial clinical relevance for pre-menopausal women with cancer requiring cytotoxic chemotherapy. Because CRA can impact prognosis [14], fertility [15], and menopausal symptoms [16], in women with breast cancer, pre-chemotherapy AMH measurement may ultimately have utility in clinical decision-making. Furthermore, identifying a pre-treatment predictor of later ovarian dysfunction could be particularly important for reproductive decision-making, as the commonly recommended fertility preservation techniques for breast cancer patients (e.g., oocyte and embryo cryopreservation) are most effective before gonadotoxic therapies are given.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of chemotherapy on ovarian function have been studied most extensively in breast cancer. [7][8][9][10][11][12] However, the effect of FOLFOX and XELOX on ovarian function and specifically on the menstrual cycle is not well studied in patients with CRC.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The effects of chemotherapy on ovarian function have been studied most extensively in breast cancer. [7][8][9][10][11][12] However, in CRC, there is currently only 1 study, to our knowledge, that tested the effects of adjuvant chemotherapy on female fertility. Cercek et al reported that 16% of women younger than 50 years had persistent amenorrhea 1 year after completion of mFOLFOX6.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, nowadays, the incidence of BC is increasing thus affecting higher numbers of younger women. For these young women affected by chemotherapy-induced menopause (CIM), an ovarian dysfunction due to chemotherapy has been highlighted [3][4][5][6][7][8] . Chemotherapy induces the reduction of ovarian follicles.…”
Section: Introductionmentioning
confidence: 99%